DYSTOCIA DUE TO PARTIAL PRIMARY UTERINE INERTIA IN A SIBERIAN HUSKY AND ITS MANAGEMENT BY CAESARIAN SECTION - BHAT, G R; DAR, S H; AHMAD, R A; FAZILI, M R (The Indian Journal of Animal Reproduction, 2023)
Husky, a popular working dog has very low incidence of dystocia associated with uterine inertia. The present report describes dystocia due to partial primary uterine inertia in a Husky bitch and its management by Caesarian section